How Sri Lanka Promotes Cultural Values through Social Media (Especial Reference to Selected YouTube Channels) - Lokumannage, Amila (European Journal of Science, Innovation and Technology, 2024)
This study examined how Sri Lanka portrayed culture in perspective of world tourism through YouTube. Central to the study is to find out what ways videos and information are used on promoting Sri Lankan culture through YouTube. YouTube videos which were published in 2023/2024 analyzed YouTube channels and the selected YouTubers were interviewed. An analysis of traveling videos of YouTubers was done to ascertain how Sri Lanka is portrayed in context of global tourism. The interviews and text analysis provided data needed to answer the research questions. Previous research findings and the text analysis revealed that the Sri Lanka YouTubers mostly introduce Sri Lanka as a destination for diving area and didn’t create a special channel for traveling. In conclusion the study suggested different areas for improvement so as to make Sri Lankan YouTubers more effective on advertising the tourism industry of the country globally as well as constructively attracting local people to engage as operators in tourism related business, while at the same time painting the image of the country so as to attract more foreign tourists.
Keywords: Sri Lanka; Tourism; Social Media; Culture; YouTube